‘Belimpun Taka Tugas, Insuai Taka Tapu’: Orang Tidung, Marginalisasi dan Perlawanan di Pulau Sebatik Nunukan - usman idrs (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2017)
The struggle among various ethnic groups socially forms ethnic stratification and contestation discourse. This article aims to explore Tidung movement as native inhabitants, but marginalised minority in order to get involved in the struggle of power relations in Pulau Sebatik which has been dominated by migrants. The study indicates that as minority group, Tidung people is stereotyped by other ethnic group as lazy, slow, less educated, and under develop. These marginalised them in many aspects of life, particularly in economics, politics, land tenure. In responding to this, Tidung people establish a movement to develop symbolic investation strategy, so that they have a space in rhe struggle of power relations in Pulau Sebatik. The movement unites sub-ethnic Tidung, namely Sebuku, Sembakung, dan Sesayap by establishing FKWT - Forum Komunikasi Warga Tidung (Communication Forum of Tidung People) and LAT - Lembaga Adat Tidung (Customary Institution of Tidung) in order to legitimate their power as indigeneous people. Then, customary forest is claimed as the symbol to gain their right for forest management. They also gain prestige by getting involved in the border conflict between Malaysia and Indonesia through which they can show that they contribute in maintaining state sovereignity.